العقاب البدني للطفل بين العنف والتربية - ابراهيمي, كوثر; بوعمر, سهيلة (Changement Social, 2018)
نسعى من خلال هذا البحث إلى توصيف العقاب البدني من حيث مفهومه ومدى انتشاره محليا وعربيا وعالميا، وطرح مسألة كون هذا الأسلوب هو تربوي أم تعنيفي من خلال عرض لما توصلت له الدراسات من تأثيرات العقاب البدني على الطفل، مع وضعها في إطار الانتقادات التي وجهت لها، لنتوصل في الأخير إلى الإجابة عن هذا الإشكال ووضع هذا النوع من العقاب في موضعه الصحيح. مع التطرق إلى أساليب العقاب البدني المعتمدة من الأسرة الجزائرية. This paper description about the  Concept of corporal punishment and his locally, Arabian and worldwide relevance  , and we discussion if this method is education or violence . The research studies shows many effects of  corporal  punishment  to child, and there is many criticisms we will be described, and finally answer the  problematic for this type of method  , in addition we explanation about  the ways of corporal punishment  for Algerian families.